Information Seeking Behaviour of Engineering College Students: A Case Study - Ramaiah, Chennupati K; Shimray, Simipam R (DESIDOC Journal of Library & Information Technology, 2018)
The purpose of this study is to evaluate the use of various services and facilities provided by Muffakham Jah College of Engineering and Technology Library, Hyderabad, India. This study used survey method and questionnaire tool for data collection. The majorities of the respondents in this study choose print form of textbooks (78 %) and printed reference books (80.33 %). Of the total, 80 per cent of them stated that they did not find any gaps in library collections. It was found that most of them (93.33 %) do not find any problems and issues in accessing information from the available resources. The majority (89 %) of them agreed with the working hours and 81.67 per cent of the respondents are satisfied with the services offered by the library staff. Over three fourths (78.67 %) of them are satisfied with the existing facilities provided by the library. The majority (89 %) of the respondents indicated that the library should have a separate website in addition to the college website.